La constitucionalización de los derechos del consumidor en Colombia: un análisis desde los derechos sociales fundamentales. (2013)
This article provides an analysis for a proper constitutional categorization of consumer rights in Colombia and the identification of each of the elements; acts and relationships that truly integrate the consumer relations; which in turn demand; by their own nature; an individual ownership; to ensure a decent standard of consumption; in which the dignity of each person requires respect for personal and economic freedom; satisfying the social order in the sense of allowing the domain of a minimum living space and socioeconomic status to the individuals so facilitating a harmonious and balanced coexistence in terms of production; marketing; distribution and procurement of goods and services.